Dairy Business Analysis Project: 2001 Financial Summary - Albert De Vries; Russell Giesy; L. Ely; A. de Araujo; Andy Andreasen; Brent Broaddus; Shepard Eubanks; Doug Mayo; P. Miller; Travis Seawright; Chris Vann (EDIS)
This publication is a summary of the financial performance in the year 2001. It is intended for general use by dairy farmers, the allied industry, and government, and educational professionals. This document is AN136, one of a series of the Animal Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published January 2003.